Analysis of minor actinides transmutation for a Molten Salt Fast Reactor. (November 2015) - Yu, Chenggang; Li, Xiaoxiao; Cai, Xiangzhou; Zou, Chunyan; Ma, Yuwen; Han, Jianlong; Chen, Jingen
Highlights: The transmutation of MA in a 500 MWth MSFR is analyzed. A larger MA loading can enhance the MA transmutation and deepen the burnup. The MA transmutation efficiency can reach 95%. The FTC can satisfy the safe operating requirement during the entire operating. Abstract: As one of the six candidate reactors chosen by the Generation IV International Forum (GIF), Molten Salt Fast Reactor (MSFR) has many outstanding advantages and features for advanced nuclear fuel utilization. Effective transmutation of minor actinides (MA) could be attained in this kind of fast reactor, which is of importance in the future closed nuclear fuel cycle scenario. In this work, we attempt to study the MA transmutation capability in a MSFR with power of 500 MWth by analyzing the neutronics characteristics for different MA loadings. The calculated results show that MA loading plays an important role in the reactivity evolution of the MSFR. A larger MA loading is favorable to improving the MA transmutation performance and simultaneously to reducing the fissile consumption. When MA = 18.17 mol%, the transmutation fraction can achieve to about 95% on iso-breeding. We also find that although the fuel temperature coefficient (FTC) decreases with the increasing MA loading, it is still negative enough to keep the safety of the MSFR during the whole operation time. The MA contribution to the effective delayed neutron fraction (EDNF) and the intensity of spontaneous fission neutron (ISFN) are also analyzed. Also MA loading can affect the EDNF during the operation and the ISFN of the MSFR is dominated by 244 Cm. Finally, we analyze the effect of the core power on MA transmutation capability. The result shows that for all the operating powers the depletion ratio of MA to HN increases with time and reaches a maximum value. And additional MA should be fed into the fuel salt before the MA depletion ratio reaches the peak value to improve its transmutation capability. The net mass of the transmuted MA during the 50 years operation for 500 MWth is 5620 kg which is very close to that of 1000 MWth.